2022
DOI: 10.1021/acs.jnatprod.1c01231
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Plant Ingredient, Menthone, Regulates T Cell Subtypes and Lowers Pro-inflammatory Cytokines of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease with nearly 1.6 billion patients worldwide and an incidence of 0.5−1%. In recent years, basic and clinical studies have revealed that immune cell responses and corresponding secretion of inflammatory factors are important in the control of RA development. Our study found that a natural plant ingredient, menthone, could be used as a potential antirheumatism compound. In vivo observations demonstrated that menthone alleviates collagen II-induced arthritis (CIA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…A study by Karimian et al [ 66 ] demonstrates that another mint species, M. longifolia , likely reduces NO secretion in macrophages by inhibiting iNOS mRNA expression and also decreases the expression of pro-inflammatory cytokines such as TNF, thus, showing its utility in inflammatory disease processes. The most likely cause of this biological activity is menthone; in fact, a recent study in mice with artificially induced arthritis found that menthone significantly reduced the release of cytokines that promote inflammation, including TNF-, IL-1, and IL-6 [ 67 ].…”
Section: Studies Researchmentioning
confidence: 99%
“…A study by Karimian et al [ 66 ] demonstrates that another mint species, M. longifolia , likely reduces NO secretion in macrophages by inhibiting iNOS mRNA expression and also decreases the expression of pro-inflammatory cytokines such as TNF, thus, showing its utility in inflammatory disease processes. The most likely cause of this biological activity is menthone; in fact, a recent study in mice with artificially induced arthritis found that menthone significantly reduced the release of cytokines that promote inflammation, including TNF-, IL-1, and IL-6 [ 67 ].…”
Section: Studies Researchmentioning
confidence: 99%